IDENTIFIKASI ZAT WARNA SINTETIS PADA AGAR-AGAR TIDAK BERMERK YANG DIJUAL DI PASAR DORO PEKALONGAN DENGAN METODE KROMATOGRAFI KERTAS - Endang Triwahyuni M; Erna Susilowati (JURNAL LITBANG, 2006)
The increasing numbers of small industries and home industries which processes food products are often tollowed by cases of chemical substances misuse. The process involves synthetic coloring substantive in order to get the expected product, for both for the producer andthe consumer.Jelly is a thick substantive made of seaweed. To make it, we only need to heat the jelly Jlour in boiling water, After it gets cold it will turn into gel and csn be formed the way we like it To add more Jlavors we can add natural or synthetic additional substances for coloring and sweetener onthe process.This research is dedicated to identify the types of synthetic coloring substantive added to jelliesand to compare the result with Permenkes RI No. 722 / PER / 1988.This is a descriptive research, using chromatograph paper method to check the qualitative test on the synthetic coloring substantive used. Population of the research is the jellies sold at Pasar Doro Pekalongan, with 4 (four) out of 5 (ive) colors taken as the sample purposively from each packages sold there.The data is taken from laboratory test, and conveyed in descriptive way. Result on laboratory test on jellies sold at Pasar Doro Pekalongan is that they uses Eritrosin, Green S, Sunset Yellow, Tartrazin, and Carmoisin as the synthetic coloring substantives as stated in Permenkes RI No.722 / MENKES / PER/ IX/ 1988.Keywords : synthetic coloring substantive, jelly, paper chromatograph.